EFL Students’ Perception on The Use of TED Talks to Enhance Speaking Skills - Azzahra, Hasna; Usysyifa, Rahma Aulia; Maulidha, Fadhilatul (Darussalam English Journal (DEJ), 2025)
Learning English for EFL students requires more than just vocabulary and grammar; it also needs confidence and fluency. This study explores how students view TED Talks as a tool to help improve their speaking skills. A qualitative descriptive method was used, with data gathered from university students through semi-structured interviews. The results show that TED Talks help them improve pronunciation, fluency, and speaking confidence. They also learn from authentic English input, noticing how speakers use intonation, gestures, and organize their ideas in presentations. Students reported feeling more motivated to practice speaking because they could see real examples of effective communication. They also appreciated being able to manage their own learning by choosing talks and strategies that suited them. However, they faced some challenges, such as fast speech, unfamiliar vocabulary, and varied accents. To handle these difficulties, they used strategies like replaying videos, using subtitles, taking notes, and practicing independently. Overall, the study concludes that TED Talks can be an effective supplementary resource for speaking practice when combined with supportive activities and guidance from teachers to help learners maximize the benefits. Keywords: TED Talks; EFL; Speaking Skills; Student Perception; Language Learning